Enhancement of Optoelectronic Properties of Multicrystalline Silicon Using Al-NPs and SiNx Layer - Mohamed Ben Rabha; Ameny El Haj; Achref Mannai; Karim Choubani; Mohammed A. Almeshaal; Wissem Dimassi (Crystals)
In this study, we investigated and compared the influence of alumina nanoparticles (Al-NPs) and silicon nitride (SiNx) layers individually deposited on multi-crystalline silicon (mc-Si) on mc-Si’s structural, optical, and optoelectronic characteristics to improve surface quality. Alumina nanoparticle-covered multi-crystalline silicon, immersion in HF/H2O2/HNO3, and porous silicon (PS) covered with a silicon nitride structure are key components in achieving high electronic quality in multi-crystalline silicon. Surface reflectivity decreased from 27% to a minimum value of 2% for alumina nanoparticles/PS and a minimum value of 5% for silicon nitride/PS at a wavelength of 930 nm. Meanwhile, the minority carrier diffusion length increased from 2 µm to 300 µm for porous silicon combined with silicon nitride and to 100 µm for alumina nanoparticles/porous silicon. Two-dimensional current mapping further demonstrated a considerable enhancement in the generated current, rising from 2.8 nA for untreated mc-Si to 34 nA for Al-NPs/PS and 66 nA for PS/SiNx. These results confirm that the surface passivation of mc-Si using Al-NPs or PS combined with SiNx is a promising and efficient method to improve the electrical quality of mc-Si wafers, contributing to the development of high-performance mc-Si-based solar cells.